2023
DOI: 10.3847/1538-4357/acc465
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multifluid Effects in the Solar Chromosphere on the Ponderomotive Force under SE and NEQ Ionization Conditions

Abstract: The ponderomotive force has been suggested to be the main mechanism to produce the so-called first ionization potential (FIP) effect—the enrichment of low-FIP elements observed in the outer solar atmosphere, in the solar wind, and in solar energetic events. It is well known that the ionization of these elements occurs within the chromosphere. Therefore, this phenomenon is intimately tied to the plasma state in the chromosphere and the corona. For this study, we combine IRIS observations, a single-fluid 2.5D ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Throughout this time period, the leading polarity region has a consistently lower associated FIP bias than the following polarity region, where the unsigned flux density is consistently below 200 G. The emerging flux region also follows this hypothesis, with an FIP bias value between that of the leading and following polarity regions and a consistent unsigned flux density value of ∼50-100 G. These observations are also comparable with the work of To et al (2023), who found a similar relationship between coronal abundance and magnetic flux density using observations of this active region from 2020 April 3-7. It is interesting that this is also consistent with the work of Martínez-Sykora et al (2023), who suggested that sunspots with strong flux densities approach a collisionless case, where waves from the chromosphere could generate an IFIP effect, thus lowering the FIP bias associated with the region (as noted here) or even creating an observable IFIP bias.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Throughout this time period, the leading polarity region has a consistently lower associated FIP bias than the following polarity region, where the unsigned flux density is consistently below 200 G. The emerging flux region also follows this hypothesis, with an FIP bias value between that of the leading and following polarity regions and a consistent unsigned flux density value of ∼50-100 G. These observations are also comparable with the work of To et al (2023), who found a similar relationship between coronal abundance and magnetic flux density using observations of this active region from 2020 April 3-7. It is interesting that this is also consistent with the work of Martínez-Sykora et al (2023), who suggested that sunspots with strong flux densities approach a collisionless case, where waves from the chromosphere could generate an IFIP effect, thus lowering the FIP bias associated with the region (as noted here) or even creating an observable IFIP bias.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the emerging flux region exhibits a much broader range of values, typically peaking at a lower value than observed for the following polarity region (with the exception here of the C II line in panel (i). As noted by Martínez-Sykora et al (2023), the Si IV line width provides insight into unresolved velocity due to Alfvén waves, so we chose the Si IV 1403 Å line width for further analysis in Section 4.…”
Section: Spectral Line Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent numerical simulations by Réville et al (2021) using a shell turbulence model found that, under the assumption that turbulence is the main driver of coronal heating and solar wind acceleration, a ponderomotive force can appear in the chromosphere and the transition region, and can be strong enough to create the FIP effect. Martínez-Sykora et al (2023) use a combination of observations from the IRIS mission (De Pontieu et al 2014) and a 2.5D radiative magnetohydrodynamics model of the solar atmosphere to investigate the multifluid effects on the ponderomotive force associated with Alfvén waves.…”
Section: Introductionmentioning
confidence: 99%